2024
DOI: 10.1002/acn3.51995
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen‐induced glial IL‐1β mediates extrinsic retinal ganglion cell vulnerability in murine Nf1 optic glioma

Yunshuo Tang,
Jit Chatterjee,
Ngan Wagoner
et al.

Abstract: Optic pathway gliomas (OPGs) arising in children with neurofibromatosis type 1 (NF1) can cause retinal ganglion cell (RGC) dysfunction and vision loss, which occurs more frequently in girls. While our previous studies demonstrated that estrogen was partly responsible for this sexually dimorphic visual impairment, herein we elucidate the underlying mechanism. In contrast to their male counterparts, female Nf1OPG mice have increased expression of glial interleukin‐1β (IL‐1β), which is neurotoxic to RGCs in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Interestingly, Jecrois and colleagues reported that either the simultaneous removal of three out of the four alleles from the Mek1 and Mek2 genes (as complete elimination of the two alleles of Mek1 and the two alleles of Mek2 proved lethal) or administration of a low-dose MEK inhibitor (PD0325901) through the lactating mother’s milk prevented NF1-OPG formation [ 201 ]. A recent report attributed the predominance of OPG formation in girls to higher levels of glial interleukin-1β, which can be suppressed by IL-1β neutralization and leuprolide-mediated estrogen suppression [ 192 , 202 ]. However, it is important to note that the formation of the optic chiasm in mice differs from humans [ 181 ] and these tissue-restrictive tumors in mice do not fully replicate the complex pathology of NF1 patients [ 203 ].…”
Section: The Role Of Animal Models To Uncover Underlying Mechanisms O...mentioning
confidence: 99%
“…Interestingly, Jecrois and colleagues reported that either the simultaneous removal of three out of the four alleles from the Mek1 and Mek2 genes (as complete elimination of the two alleles of Mek1 and the two alleles of Mek2 proved lethal) or administration of a low-dose MEK inhibitor (PD0325901) through the lactating mother’s milk prevented NF1-OPG formation [ 201 ]. A recent report attributed the predominance of OPG formation in girls to higher levels of glial interleukin-1β, which can be suppressed by IL-1β neutralization and leuprolide-mediated estrogen suppression [ 192 , 202 ]. However, it is important to note that the formation of the optic chiasm in mice differs from humans [ 181 ] and these tissue-restrictive tumors in mice do not fully replicate the complex pathology of NF1 patients [ 203 ].…”
Section: The Role Of Animal Models To Uncover Underlying Mechanisms O...mentioning
confidence: 99%